Risk-Based Post-Marketing Surveillance (RB-PMS) of antimalarial drugs and maternal, neonatal and reproductive health (MNCH) in Mali - Dembele, Ousmane; Coulibaly, Seydou Moussa; Cissé, Bakary Moussa; Cissé, Mody; Dakouo, Jacques; Cissé, Nana Houmama; Koumaré, Benoît Yaranga (Journal of Drug Delivery and Therapeutics, 2022)
Objectives: In a world marked by the increase in chemoresistance leading to the adoption of therapeutic combinations, the advent of generic multi-source drugs, the spread of counterfeiting and substandard drugs, often without active ingredients or falsified active ingredients, a Greater vigilance by pharmaceutical regulatory authorities is needed. Drug Post-Marketing Surveillance (PMS) therefore plays an important role in detecting poor quality products on the market. Risk-Based Post-Marketing Surveillance (RB-PMS) is a new form of PMS that is emerging and was the subject of a recent WHO publication. Methods: The survey covered certain regions and certain points of sale identified by a Technical Working Group. It aimed to assess the quality of antimalarial and MNCRH drugs available at certain risk distribution levels based on priority sites. The selection of drugs and geographic areas was made using risk-based sampling using the Drug Risk Assessment Tool (MedRS) developed by USP / PQM +. Results: A total of 242 samples were taken and analyzed according to a risk-based protocol, of which 233 were compliant with a rate of 96% against 9 were non-compliant or 4% (P≤0,05). Non-compliant drugs were mainly from the public sector. We found 69% of the unregistered drugs that consisted mainly of antimalarial drugs and which came from India and China. Conclusion: In view of the scarcity of resources and its scientific nature, this risk-based sampling and analysis technique (RB-PMS) must be pursued, optimized and made sustainable to ensure health and guarantee access to quality medicines for the health and well-being of populations. Keywords: Antimalarials, MNCH, Quality Control, RB-PMS.